Atypical glomerulization in the remnants of the olfactory bulb after bulbectomy. A light microscopic study - Zigová, T; Amemori, T; Raceková, E; Marsala, J (Journal fur Hirnforschung, 1988)
Regeneration of olfactory axons after bilateral bulbectomy in adult rats leads to atypical localization of the newly formed glomeruli. These structures are localized in the remnants of the olfactory bulb either in the previously deafferented glomerular layer or between external plexiform and granule cell layers in the close vicinity of mitral cells.
Keywords: Iron; Olfactory Bulb; Rats; bulbus olfactorius; hematoxylin; zvířata; železo; regenerace nervu; Hematoxylin; Nerve Regeneration; krysa rodu Rattus; Animals